1978
DOI: 10.2151/jmsj1965.56.5_368
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on the Effects of a Mountain on the Land and Sea Breezes

Abstract: Thermal and dynamical effects of mountain on the land and sea breezes are studied numerically, by paying special attention to the growth and decay of the circulations and the extent of them. A two dimensional model in a vertical plane perpendicular to a seacoast line and a mo untain chain is used. The horizontal extent and the depth of the computational region are assumed to be 130km and 3km, respectively. The mountain is assumed to have a simple trapezoidal form with 8km in width and 450m in height, and is lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 14 publications
(5 reference statements)
1
27
0
Order By: Relevance
“…These studies have found that on a heated slope of sufficiently low steepness (less than 2.29 • according to Asai and Mitsumoto 1978 or ≈0.8 • according to Porson et al 2007b), thermally-driven slope flows may couple with sea breezes and increase u, w, l, and h (Mahrer and Pielke 1977;Estoque and Gross 1981;Miao et al 2003). Combined sea-breeze and slope flows may also lead to an earlier inland sea-breeze frontal passage (Ookouchi et al 1978;Kikuchi et al 1981). A slope of sufficiently high steepness will act to block the inland penetration of the sea-breeze front and decrease u, w, l, and h (Asai and Mitsumoto 1978;Segal et al 1983;Neumann and Savijarvi 1986;Porson et al 2007b).…”
Section: Terrain Height (H T ) and Slope (S)mentioning
confidence: 98%
See 2 more Smart Citations
“…These studies have found that on a heated slope of sufficiently low steepness (less than 2.29 • according to Asai and Mitsumoto 1978 or ≈0.8 • according to Porson et al 2007b), thermally-driven slope flows may couple with sea breezes and increase u, w, l, and h (Mahrer and Pielke 1977;Estoque and Gross 1981;Miao et al 2003). Combined sea-breeze and slope flows may also lead to an earlier inland sea-breeze frontal passage (Ookouchi et al 1978;Kikuchi et al 1981). A slope of sufficiently high steepness will act to block the inland penetration of the sea-breeze front and decrease u, w, l, and h (Asai and Mitsumoto 1978;Segal et al 1983;Neumann and Savijarvi 1986;Porson et al 2007b).…”
Section: Terrain Height (H T ) and Slope (S)mentioning
confidence: 98%
“…The earliest hydrostatic models used simple boundary-layer schemes and neglected moisture, latent heating, radiation, and land-surface parametrisations. Some later models included radiation, moisture and latent heating, with increasingly sophisticated schemes for surface heating and the turbulent Neumann andMahrer (1971, 1974) 5 , Pearson (1973) Pielke (1974a,b) 4 1975-1979 2D 2.5-8 9 Neumann and Mahrer (1975) 5 , Sheih and Moroz (1975) 1 , Estoque et al (1976) 1 , Pielke (1976, 1977) 3 , Physick (1976) 4 , Anthes (1978) 2 , Asai and Mitsumoto (1978) 1 , Ookouchi et al (1978) 3 1980-19842D 3-10 8 Physick (1980 4 , Estoque and Gross (1981) 1985-1989 2D 1-10 14 Garratt and Physick (1985) 2 , Mahrer and Segal (1985) 1 , Physick and Smith (1985) 3 , Neumann and Savijarvi (1986) 1 , Noonan and Smith (1986) 2 , Segal et al (1986) 3 , Arritt (1987Arritt ( , 1989 4 , Briere (1987) 1 , Anthes (1987, 1988) Freitas et al (2007) 8 , Srinivas et al (2007) 8 , Talbot et al (2007) 8 , Thompson et al (2007) 8 , Cheng and Byun (2008) transport of heat, moisture, and momentum. Through the 1970s, turbulence in the surface layer was generally treated using simple K-theory, assuming constant fluxes, and with empirical formulations for turbulent transport in the overlying transition layer.…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…The first term in (2.2.7); the vertical shear of a zonal flow, is neglected as it is much smaller than the second stability term. We assume that l is constant in the atmosphere and is decided to 50m by the convective instability considerations (see Ookouchi et al, 1978). Thus, when the stratification becomes unstable, KM or KH in the transition layer above z=50m is shown as follows, using *a= 302*K as the representative potential temperature in the middle layer of the model:…”
Section: Basic Equations Systemmentioning
confidence: 99%
“…From the computations for the horizontal orographic effect (McPherson, 1970;Pielke, 1974;Takano, 1976;etc. ) and for the vertical orographic effect (Asai et al, 1978;Ookouchi et al, 1978;Kikuchi et al, 1981;etc. ) to the land and sea breeze, it has been shown that there was the ascending flow region at 10km inland across the coast, and the head of this region is sometimes termed the sea-breeze front.…”
Section: Introductionmentioning
confidence: 99%